Ligninase Profiling and Optimization of Laccase Production from Indigenous Wood Rot Fungus (WRF) KLUM2 in Kirk Medium-Alkali Lignin Kayu Jati (MK-ALKJ) - Siti Mutmainah; Evi Susanti (Jurnal Kimia Valensi, 2021)
The production of ligninase by wood rot fungus (WRF) is determined by carbon source and growth condition. The goal of this study is to determine the ligninase profile produced by WRF KLUM2 in Kirk Medium using teak wood alkaline lignin as a carbon source known as Kirk Medium-Alkali lignin Kayu Jati (MK-ALKJ), optimization of dominant ligninase production in the MK-ALKJ compared to the one that is produced in the Kirk’s medium with glucose as a carbon source (MK-Glucose). This research was conducted in an experimental laboratory consisting of: (1) spore suspension preparation, (2) ligninase profiling at various growth times, (3) ligninase profiling at various temperature variations, (4) optimization of laccase production including pH and the amount of nitrogen source. Growth was identified based on the specific activity of lignin peroxidase (LiP), manganese peroxidase (MnP), and laccase. The results showed that relatively the three types of ligninase, namely LiP, MnP, and laccase, were produced in the same amount by the wood rotting fungus isolates KLUM2 in MK-ALJK. All three were produced with the highest yield of respectively 55.65; 52.48; 57.64 U/mg. Laccase as the dominant ligninase can be optimized to reach 83.52 U/mg by inoculating 2.107 spore cells in MK-ALKJ in 37 °C, pH = 3.5, and a nitrogen source of 20mM (NH4)2SO4 for 6 days. Therefore, it can be concluded that the ligninase activity of indigenous WRF KLUM2 in MK-ALJK medium is higher than in the MK-Glucose.